2099 E. coli Sepsis Following FMT in an IgA Deficient IBD Subject - Glover, Sarah C.; Burstiner, Shane; Jones, Demarre; Teymoorian, Arian; Naga, Yehia; Silver, Jared; Pallav, Kumar (The American journal of gastroenterology, 2019)
INTRODUCTION:Fecal microbiota transplant (FMT) has been demonstrated to be an effective treatment option for recurrent C. difficile infections (RCDI) with minimal serious adverse reactions reported. Although the results of FMT for RCDI are promising, the screening process (for both donors and recipients) remains largely unregulated by the FDA.CASE DESCRIPTION/METHODS:A 19 y.o. male with a history of primary IgA deficiency, growth hormone deficiency, asthma, and ulcerative colitis presented to his gastroenterologist with his 3rd C. difficile infection in a 4 month period. FMT was performed via colonoscopy using commercially sourced stool. 10 days later, the patient presented to the ER with explosive bloody diarrhea, up to 20 BMs per day. He was also positive for leukocytopenia, tachycardia, intermittent subjective fevers, chills, night sweats, and abdominal cramping. Stool studies were positive for EPEC, ETEC, and Shiga toxin-producing E. coliO157:H7. Patient was not given antibiotics and received supportive care for 17 days until discharge. He has a good prognosis and has not experienced a recurrence of CDI since the FMT 3 months ago. Unbeknownst to his Gastroenterologist, the patient had a history of mostly asymptomatic, total primary IgA deficiency that was diagnosed in the Czech Republic.DISCUSSION:This appears to be the first reported instance of an individual with Primary IgA Deficiency undergoing FMT and also the first reported instance of FMT-introduced E. coli O157:H7 infection. The patient’s complete lack of IgA appears to be the main catalyst for his disastrous response to FMT. While barrier defects secondary to IBD and the concomitant use of immunosuppressive medications (Xeljanz and Entyvio) can increase susceptibility to infections, studies have shown FMT does not carry an increased risk of serious adverse effects in immunocompromised patients (including IBD patients on immunosuppressive therapy). This patient was not screened for immunodeficiencies prior to receiving FMT. The FDA has issued guidelines, but does not currently mandate which pathogens the stool must be screened for, or which comorbidities the recipient must be screened for. Given the understood importance of IgA in mucosal immunity against E. coli, and the outcome presented in this study, we suggest that rigorous screening of the recipient's medical history for immunodeficiency, and/or potentially running a basic Immunoglobulin panel, should be considered prior to performing FMT.